2017
DOI: 10.1177/0165025417741366
|View full text |Cite
|
Sign up to set email alerts
|

The understanding of emotion among young Chinese children

Abstract: The development of emotion understanding in young Chinese preschoolers was examined. The overall developmental trend, as measured by the Test of Emotion Comprehension (TEC), proved similar to that found among preschoolers in Western Europe. However, Chinese children performed better at understanding the distinction between real and apparent emotion and worse at understanding the connection between reminders and emotion. Children’s theory of mind and verbal ability were significant predictors of their ability t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 33 publications
3
22
0
2
Order By: Relevance
“…In a cross‐cultural study using the TEC (Pons & Harris, 2000) to asses cultural differences in phases of emotional development, Tang, Harris, Pons, Zou, Zhang and Xu (2018) found that Chinese children ( N = 65; age = 4–6), developed an understanding of emotions that followed a pattern similar to that found in Western European preschoolers. Chinese preschoolers did, however, perform better at understanding hidden emotions compared to European children, and worse at linking reminders to emotions.…”
Section: Parental Emotion‐related Socialization Behaviors (Ersbs)mentioning
confidence: 97%
“…In a cross‐cultural study using the TEC (Pons & Harris, 2000) to asses cultural differences in phases of emotional development, Tang, Harris, Pons, Zou, Zhang and Xu (2018) found that Chinese children ( N = 65; age = 4–6), developed an understanding of emotions that followed a pattern similar to that found in Western European preschoolers. Chinese preschoolers did, however, perform better at understanding hidden emotions compared to European children, and worse at linking reminders to emotions.…”
Section: Parental Emotion‐related Socialization Behaviors (Ersbs)mentioning
confidence: 97%
“…С разрешения авторов данная методика была переведена на русский язык (подробное описание методики представлено ниже). Методика переведена на 21 язык и широко используется исследователями в Англии, Италии, Бразилии, Китае, Норвегии и других странах (Albanese et al, 2006;Tang et al, 2018;Fidalgo et al, 2018), что обеспечивает возможность проведения международных исследований. Работы, проведенные с использованием данного теста, показали, что он обладает хорошей надежностью и конструктной валидностью (например: Tang et al, 2018).…”
Section: резюмеunclassified
“…Как и в оригинальной версии теста, в русскоязычной выборке не были выявлены гендерные различия ни по одному из компонентов теста. Аналогичные результаты были получены при адаптации данного теста на итальянской, английской и китайской выборке (Albanese et al, 2006;Tang et al, 2018;Fidalgo et al, 2018).…”
Section: обсуждение и заключениеunclassified
“…But it is only from around 8 to 10 years of age that they become able to understand moral and mixed emotions, and the possibility to regulate emotions by the mean of psychological strategies. Despite individual and cultural variations in emotion understanding development, this hierarchical organization has been found across different cultures (for a review, see Tang et al, 2018). Recent studies have also indicated that children's emotion understanding is an important predictor of their psychological well-being (e.g.…”
Section: Introductionmentioning
confidence: 99%